CLINICAL AND LABORATORY EVALUATION OF VITAMIN A AND BETA CAROTENE IN LOCAL SHEEP BREED OF BASRA, BASRA_ IRAQ - Samar Hussain M; Mohammed A. Y. Al-Amery (Basrah Journal of Veterinary Research)
The study was conducted on (96) local sheep breeds of different ages and both gender reared in Basrah, Iraq. Suspected animals show signs of night blindness, abortion of pregnant ewes, diarrhea with passing of normal small fecal materials ,nervous sings (such as paralysis of skeletal muscles, blindness due to constriction of the optic nerve canal, convulsions encephalopathy). Moreover diseased animals were also show panting and changing of skin .The levels of vitamin A and Beta carotene were estimated by ELISA test and results showed that local sheep suffer from hypo vitaminosis A with mean level of( 1.8 nmol/l). However according to regions of Basrah deficiency of vitamin A and carotenes respectively were indicated of center of Basra (1.7nmol/land 11.2 ng/ml). AlQurna (1.7 nmol/l and 15.9 ng/ml) .Azzubair (2.1 nmol/l and 26.3 ng/ml). Shateelarab (1.2nmol/l and 17.7 ng/ml).and Abulkhaseeb (2.0 nmol/l and 16.8ng/ml) It have been concluded that local sheep breeds of Basra province were suffer from hypovitaminosis A, therefore animals reared in those area should be screened periodically.